Model Based Research of Dynamic Performance of Shaft-Bearing System in High-Speed Field - Teng Hu; Guofu Yin; Mingnan Sun (Shock and Vibration)
Dynamic performance of the high-speed running shaft-bearing system (SBS) is different from that of idle state system due to the high-speed effects (HSE), including shaft centrifugal force, gyroscopic moment, and nonlinear bearing operational stiffness. In this paper, aiming at improving the operation stability, dynamic performance of SBS operating in high-speed field is investigated based on a finite element (FE) dynamic model. Firstly, the Timoshenko beam elements are applied to develop the SBS FE model with full consideration of HSE. Secondly, idle state frequency response function at the front tip is obtained analytically and experimentally to validate that the FE model can illustrate the system dynamic behaviors in static condition. Finally, by substituting various rotational velocities into the FE model, the HSE on system natural frequencies are studied one by one as well as together. The results show that, when bearing is being extremely light preloaded, SBS frequencies are affected by the HSE of shaft more than bearing, especially where the gyroscopic moment effect of shaft is the most influential factor. Moreover, the nonmonotonic variation of bearing operational stiffness is analyzed. The “stiffen” phenomenon explained in this paper provides a more comprehensive understanding of the nonlinear bearing operational stiffness.